2016
DOI: 10.1111/prd.12175
|View full text |Cite
|
Sign up to set email alerts
|

Current state of the art of computer‐guided implant surgery

Abstract: The invention of computerized axial tomography (now known as computerized tomography) and developments of interactive software to allow virtual planning, with the aim to guide the surgery precisely toward a specific target, has dramatically improved general, as well as oral, surgery. Virtual dental implant planning allows for a prosthetically driven approach, resulting in the best possible design of the prosthesis, better esthetics, optimized occlusion and loading. This approach has also changed the surgical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
285
2
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(347 citation statements)
references
References 55 publications
3
285
2
10
Order By: Relevance
“…This treatment modality may eliminate the need for bone grafting, and even raising a flap, if appropriate bone dimension and morphology exists . This might, in turn, improve patient acceptance to the recommended treatment and reduce post‐surgical morbidity …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This treatment modality may eliminate the need for bone grafting, and even raising a flap, if appropriate bone dimension and morphology exists . This might, in turn, improve patient acceptance to the recommended treatment and reduce post‐surgical morbidity …”
Section: Introductionmentioning
confidence: 99%
“…Despite high documented survival rates for implants placed using CGIP (approximately 95% at a 7‐year follow up period), a higher rate of prosthetic and biologic complications has also been reported . It is crucial to keep in mind that precision of implant position remains subject to the guide accuracy and adherence of the clinician to the proposed surgical protocol . Although these high‐precision technologies are used in the fabrication of such guides, several studies have shown some linear and angular deviations between the planned and placed implants .…”
Section: Introductionmentioning
confidence: 99%
“…The first surgical navigation was performed for neurosurgery by resorting to software packages developed by different research groups in previous years, which allow to visualize the human head. In the following years, a lot of improvements in this field were noted and it opened the doors to the computer-assisted surgery (CAS) development [1].…”
Section: Introductionmentioning
confidence: 99%
“…Implant‐supported fixed dental prostheses (FDPs) have been used for full‐mouth rehabilitation for decades. Virtual planning and performing treatments using computer‐aided design and computer‐aided manufacture (CAD/CAM) have been reported in full‐arch implant‐supported rehabilitation . Digital smile design technologies are popular in designing the smile from facial references and communication between the interdisciplinary team and patient .…”
mentioning
confidence: 99%